An iron law of currency crisis: the divergence of the nominal and the real exchange rate and increasing current account deficits - Horst Siebert (Kiel Institute of World Economics (IfW), 2002)
The currency crises of the 1990s all exhibit a divergence of the nominal and the real exchange rate together with an increase in the negative current account. The nominal rate does not reflect inflation differences fully and the ensuing real appreciation leads to a negative current account. This pattern holds for the Czech, the Mexican, Brazilian, Argentinian as well as the South Korean currency crises. It seems to be an iron law of currency crises.
Keywords: E0; F3; 330; real exchange rate; devaluation; currency crisis; Währungskrise; Kaufkraftparität; Leistungsbilanz; Abwertung; Mexiko; Brasilien; Argentinien; Südkorea; Tschechische Republik